2020
DOI: 10.1038/s41398-020-01072-1
|View full text |Cite
|
Sign up to set email alerts
|

Examining cognitive change in magnetic resonance-guided focused ultrasound capsulotomy for psychiatric illness

Abstract: Magnetic resonance-guided focused ultrasound (MRgFUS) anterior capsulotomy is a novel treatment option for patients with refractory obsessive compulsive disorder (OCD) or major depressive disorder (MDD). However, there is concern that lesional psychiatric surgery procedures may have adverse effects on cognition. In this study, we examined whether MRgFUS capsulotomy causes cognitive decline in patients with psychiatric illness. Ten patients with refractory OCD (n = 5) or MDD (n = 5) underwent MRgFUS capsulotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…MRgFUS capsulotomy did not adversely impact cognitive function across several domains (study with 5 OCD and 5 MDD patients) [113].…”
Section: Recommendations For Magnetic Resonance-guided Focused Ultras...mentioning
confidence: 81%
See 1 more Smart Citation
“…MRgFUS capsulotomy did not adversely impact cognitive function across several domains (study with 5 OCD and 5 MDD patients) [113].…”
Section: Recommendations For Magnetic Resonance-guided Focused Ultras...mentioning
confidence: 81%
“…Very recently, MRgFUS has been introduced into psychiatric neurosurgery [29,113]- [115]. MRg-FUS has proven efficacy, safety, and cost-efficiency for essential tremor [34,44] plus cost-efficiency for OCD [46].…”
Section: Recommendations For Magnetic Resonance-guided Focused Ultras...mentioning
confidence: 99%
“…We have found two studies from two centers reporting on MRgFUS ablative capsulotomy for refractory TRD. One (Korean group) of the two studies reported on 4 cases [69], and the other study (Toronto group) reported on 6 MDD cases [70]. Davidson et al [70][71][72] have published several papers since 2020 with overlapping patient samples.…”
Section: Post Hoc Analysismentioning
confidence: 99%
“…The Toronto group's (n = 6) [70] results have been less promising, reporting a responder rate of 20-33% at 12 months [70][71][72]. They report no significant permanent neurological, neuropsychological or psychobehavioral complications.…”
Section: Post Hoc Analysismentioning
confidence: 99%
See 1 more Smart Citation